The impact of online self-evaluation on self-awareness and lifestyle habits - Amato, Alexandre Campos Moraes; Neves, Ana Augusta Gayoso; Marinho, Larissa Serejo; Morillo, Marcos Gallan; Amato, Marisa Campos Moraes (Journal of Health Informatics, 2013)
Objective: The goal of this study was to evaluate the impact of online self-evaluation on self-awareness, alert the user about his or her risk factors for cardiovascular diseases. Methods: 195 users answered the same questionnaire in at least 2 different moments. Between the first and last time the user answered the questionnaire, there were significant changes in some of the risk factors. Results: Personal history of cardiovascular disease improved in 5.6%(P=0.97, K=0.29). Age has worsened in 9.2% which was statistically significant with almost perfect agreement (P=0.012, K=0.83). Hypertension improved in 13.3% and worsened in 16.4% of users (P=0.73, K=0.43). Obesity improved in 27.3% and worsened in 20.1% (P=0.34, K=0.45). Stress showed a statistically significant improvement of 34.4% among users and a worsening in 23.1% (P=0.20, K=0.23). Smoking improved in 22.8%(P=0.023). Physical activity increased in 29.7%. This result was statistically significant and had a fair association (P=0.0076, K=0.23). Eating habits improved in 35.9% and worsened in 35.4% (P=0.92; K=0.16). Conclusion: Virtual Check-up is a low cost evaluation method with a high impact that reaches a broad range of people. Therefore, even though the questionnaire showed small improvements in health indicators, it should be used widely.